Review of Sailing Tour Package at PT. Manumadi Wisata Labuan Bajo - Nabila Azzahra Hakim; Rahmawati Rahmawati; Hamsu Hanafi (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
This study aims: (1) To find out how the process off designing a sailing tour package at PT. Manumadi Wisata Labuan Bajo and. (2) To find out the pricing process for sailing tour packages at PT. Manumadi Wisata Labuan Bajo Tourism.. Data collection from this study was taken by the following techniques: interviews and documentation and data analysis was carried out by qualitative descriptive and drawing conclusions. In this case the author reviews the sailing tour package at PT. Manumadi Wisata Labuan Bajo, because the author sees the potential of Labuan Bajo as a one of superior tourist destination in Indonesia which has recently become a popular tourist spot that has a selling point for making tour packages so that the author was interesting in raising the title. “Review of Sailing Tour Packages at PT. Labuan Bajo Tourism Manumadi”. A tour package review, is a review of the making a tour package from the process of designing a tour package to the fixed price of a tour package to a tour package that is ready to be marketed. however, in the manufacturing process of course there are obstacles and defiance before it becomes a ready to sell tour package, so it is necessary to innovate by combining tourist attraction that is a sailing tour and a tourist attraction on land. Then it is necessary to lower the mark up a little and negotiate with various parties so that it becomes an inexpensive or affordable tour package and becomes a ready to sell tour package that is competitive for other agents.